2005
DOI: 10.1158/0008-5472.can-05-0153
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Human Embryonal Carcinomas In vitro and In vivo Reveals Expression Profiles Relevant to Normal Development

Abstract: Embryonal carcinoma is a histologic subgroup of testicular germ cell tumors (TGCTs), and its cells may follow differentiation lineages in a manner similar to early embryogenesis. To acquire new knowledge about the transcriptional programs operating in this tumor development model, we used 22k oligo DNA microarrays to analyze normal and neoplastic tissue samples from human testis. Additionally, retinoic acid-induced in vitro differentiation was studied in relevant cell lines. We identified genes characterizing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
227
1
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(243 citation statements)
references
References 29 publications
12
227
1
3
Order By: Relevance
“…Overexpression of MMSET was found in glioblastoma compared to normal brain (P = 1.7E-14, P = .009, P = .002) [11; 12; 13]; in hepatocellular carcinoma compared to normal liver (P = 2.9E-7, 1.3E-6) [14; 15]; in head and neck cancer compared to the normal (P = .008, P = 2.7E-5) [16; 17]; in bladder carcinoma compared to normal bladder (P = 4.1E-11, P = 1.8E-7) [18; 19]; in primary colon cancer compared to normal adjacent mucosa (P = 9.5E-6) [20]; in esophagus adenocarcinoma compared to normal esophagus (P = .004) [21]; in breast carcinoma compared to normal breast (P = 3.8E-8) [22]; in T-cell acute lymphoblastic leukemia compared to normal bone marrow (P = 5.1E-7) [23]; in B-cell acute lymphoblastic leukaemia compared to normal bone marrow (P = .001) [23]; in lung adenocarcinoma compared to normal lung (P = .009, P = 8.4E-4, 1.7E-6) [24; 25; 26]; in lymphoma compared to normal B-cell (P = 3.5E-5, 7.3E-5) [27]; in cutaneous melanoma compared to normal melanocyte ( P = 6.46E-13, P = .01, P =.009) [28; 29; 30]; in smoldering multiple myeloma compared to normal bone marrow (P = 7.3E-4) [31]; in prostate cancer compared to normal prostate (P = 1.8E-6, P = .039, P = 5.1E-8, P = .002, P = .009, P = .006, P = .009) [32; 33; 34; 35; 36; 37; 38]; in yolk sac tumor compared to normal testis (P = .003) [39]; in ovarian carcinoma compared to normal ovary (P = .002, P = 1.1E-4) [40; 41] and in clear cell carcinoma compared to normal kidney tissue (P = .006) [42].…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of MMSET was found in glioblastoma compared to normal brain (P = 1.7E-14, P = .009, P = .002) [11; 12; 13]; in hepatocellular carcinoma compared to normal liver (P = 2.9E-7, 1.3E-6) [14; 15]; in head and neck cancer compared to the normal (P = .008, P = 2.7E-5) [16; 17]; in bladder carcinoma compared to normal bladder (P = 4.1E-11, P = 1.8E-7) [18; 19]; in primary colon cancer compared to normal adjacent mucosa (P = 9.5E-6) [20]; in esophagus adenocarcinoma compared to normal esophagus (P = .004) [21]; in breast carcinoma compared to normal breast (P = 3.8E-8) [22]; in T-cell acute lymphoblastic leukemia compared to normal bone marrow (P = 5.1E-7) [23]; in B-cell acute lymphoblastic leukaemia compared to normal bone marrow (P = .001) [23]; in lung adenocarcinoma compared to normal lung (P = .009, P = 8.4E-4, 1.7E-6) [24; 25; 26]; in lymphoma compared to normal B-cell (P = 3.5E-5, 7.3E-5) [27]; in cutaneous melanoma compared to normal melanocyte ( P = 6.46E-13, P = .01, P =.009) [28; 29; 30]; in smoldering multiple myeloma compared to normal bone marrow (P = 7.3E-4) [31]; in prostate cancer compared to normal prostate (P = 1.8E-6, P = .039, P = 5.1E-8, P = .002, P = .009, P = .006, P = .009) [32; 33; 34; 35; 36; 37; 38]; in yolk sac tumor compared to normal testis (P = .003) [39]; in ovarian carcinoma compared to normal ovary (P = .002, P = 1.1E-4) [40; 41] and in clear cell carcinoma compared to normal kidney tissue (P = .006) [42].…”
Section: Resultsmentioning
confidence: 99%
“…Ectopic expression of Nanog leads to dedifferentiation and blocks further developmental processes (Taranger et al, 2005). Malignant transformation of teratocarcinomas and germline tumors are caused by ectopic expression of Nanog (Almstrup et al, 2004;Hoei-Hansen et al, 2005;Skotheim et al, 2005). Overexpression of the full-length retrogene Nanog P8 has been identified in a large variety of different solid tumors or cancer cell lines .…”
Section: Discussionmentioning
confidence: 99%
“…These markers are now commonly used in the clinical setting to help identify CIS in surgical biopsies. More recently, the expression profiles of CIS cells studied by microarrays (Almstrup et al, 2004;Skotheim et al, 2005) provided a series of candidate marker genes, such as TFAP2C (AP2γ) (Hoei-Hansen et al, 2004), which has shown promising results as a possible marker of CIS cells in semen samples (Hoei-Hansen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%